2017
DOI: 10.12688/f1000research.13314.1
|View full text |Cite
|
Sign up to set email alerts
|

Early language development in preterm children without neurological damage: a longitudinal study

Abstract: Children born at a very low gestational age, even those without neurosensory damages, are at risk of linguistic disorders. This longitudinal study aimed at analyzing communicative and language abilities in preterm children during their second year of life, through a standardized questionnaire, with particular attention to the communicative and language abilities that predict the first verbal skills. Our results showed that preterm children are slower than full-terms in language acquisition particularly at earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
0
8
0
5
Order By: Relevance
“…A direct and automatic matching process between an observed action and past self-related motor experiences allows the observer to understand others’ behavior, as well as their underlying intentions ( Fabbri-Destro and Rizzolatti, 2008 ; Rizzolatti and Fabbri-Destro, 2008 ; Cacioppo et al, 2017 ). A longitudinal study showed the appearance and the development of the abilities of children to understanding the intentions of mothers in the first 2 years of life ( Capobianco and Cerniglia, 2017 ; Capobianco et al, 2017 ), which indicated that gesture-speech combinations play specific roles in children’s early language development. This result is consistent with Liew et al’s conclusion that the MNS also plays a key role in language-related abilities ( Liew and Aziz-Zadeh, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…A direct and automatic matching process between an observed action and past self-related motor experiences allows the observer to understand others’ behavior, as well as their underlying intentions ( Fabbri-Destro and Rizzolatti, 2008 ; Rizzolatti and Fabbri-Destro, 2008 ; Cacioppo et al, 2017 ). A longitudinal study showed the appearance and the development of the abilities of children to understanding the intentions of mothers in the first 2 years of life ( Capobianco and Cerniglia, 2017 ; Capobianco et al, 2017 ), which indicated that gesture-speech combinations play specific roles in children’s early language development. This result is consistent with Liew et al’s conclusion that the MNS also plays a key role in language-related abilities ( Liew and Aziz-Zadeh, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the child’s significant inability to speak in specific social situations (for instance at school) or in non-familiar circumstances. The clinical and research data confirm that SM is a complex etiological multifactorial disorder whose maintenance is connected with the interaction of biological (familiarity with shyness, preterm birth) ( Capobianco & Cerniglia, 2017) and environmental early factors (anxiety and overprotectiveness of the mother) ( Capobianco et al , 2010; Capobianco et al , 2017; Capozzi et al ., 2017; Pizzuto & Capobianco, 2008) Analysis of the underlying thoughts and emotions in mutacic behavior reveals fear of judgment, fear of failure and being mocked, shame, depression, feelings of worthlessness or inadequacy , catastrophizing, and confirms the comorbidity between selective mutism and internalizing symptoms. The typical age of onset for selective mutism is between 3–6 years, even though the disorder gets usually diagnosed belatedly during the school age (around 7–8 years).…”
Section: Introductionmentioning
confidence: 76%
“…The typical age of onset for selective mutism is between 3–6 years, even though the disorder gets usually diagnosed belatedly during the school age (around 7–8 years). It seems that the twins condition in presence of frequent associated additional biological and environmental conditions (prematurity, maternal stress, isolation) plays a crucial role in aggravating mutacic difficulties ( Capobianco & Cerniglia, 2017; Capobianco & Cerniglia, 2018). The possibility to improve and change the symptomatology of SM-diagnosed children is strongly related to the severity of the disorder and the biological environmental factors implicated in each single case.…”
Section: Introductionmentioning
confidence: 99%
“…O impacto da prematuridade, no processo de desenvolvimento da criança, é evidenciado pelos problemas de desenvolvimento associados à menor idade gestacional (Caravale, Mirante, Vagnoni, & Vicari, 2012;Jones, Champion & Woodward, 2013). A análise de trajetórias de desenvolvimento de crianças que nasceram pré-termo, quando comparadas às crianças nascidas a termo, mostra que as primeiras têm mais problemas em áreas relevantes do desenvolvimento tais como: atraso do neurodesenvolvimento (Vieira & Linhares, 2011), problemas cognitivos (Wolke, Samara, Bracewell, Marlow & EPICure Study Group, 2008;Luu et al, 2009;Mansson, Stjernqvist, & Backstrom, 2014;Delane et al, 2016;Ionio et al, 2016;Jones et al, 2013;Lee, Pascoe & McNicholas, 2017), dificuldades de linguagem (Wolke et al, 2008;Luu et al, 2009;Manson & Stjernqvist, 2014;Woods, Rieger, Wocadlo, & Gordon, 2014;Ionio et al, 2016;Capobianco & Cerniglia, 2017), problemas de aprendizagem (Grunau, 2002;Wolke et al, 2008;Salt & Redshaw, 2006), dificuldades motoras (Mansson & Stjernqvist, 2014;Miyagishima et al, 2016;Lee et al, 2017) e dificuldades comportamentais e emocionais (Hack et al, 2009;Linhares, Chimello, Bordin, Carvalho & Martinez, 2005). Em especifico, os problemas de comportamento podem ser identificados nos três primeiros anos da criança (Delobel-Ayoub et al, 2006), na fase pré-escolar (Jones et al, 2013) e na fase escolar (Linhares et al, 2005;Treyvaud et al, 2013), sendo mais frequentes na população de crianças nascidas pré-termo, quando comparadas às crianças nascidas a termo.…”
Section: Contexto Teórico-conceitual Para Compreensão Dos Riscos Da Punclassified